Effect of locally delivered tetracycline hydrochloride as an adjunct to scaling and root planing on Hba1c, C-reactive protein, and lipid profile in type 2 diabetes: A clinico-biochemical study - Vidya Dodwad; Sakshi Ahuja; Bhavna Jha Kukreja (Wolters Kluwer Medknow Publications, 2012)
Aim: The aim was to assess the levels of HbA1c, C-reactive protein, and lipid profile in patients with type 2 diabetes mellitus by treating the pockets using collagen impregnated sustained release resorbable tetracycline fiber (periodontal plus AB fiber) following scaling and root planing (SRP). Materials and Methods: A total of 40 patients with type 2 diabetes mellitus were randomly distributed into two groups receiving either SRP and tetracycline fiber or SRP alone. Patients were evaluated clinically with gingival index, plaque index, probing depth, and relative attachment level, and bio-chemically with HbA1c, C Reactive Protein, and lipid profile at baseline, 1 month, and 3 months. Results: Significant reduction in all the clinical parameters was seen in the tetracycline group compared to the control group. Bio-chemical analysis also revealed similar results except for cholesterol and High density lipoprotein who did not show any significant reduction. Conclusion: Locally delivered tetracycline as a better treatment modality compared to SRP alone.